Debt's Dominion : a History of Bankruptcy Law in America. - Skeel, David A., Jr (Princeton University Press, 2014)
Bankruptcy in America, in stark contrast to its status in most other countries, typically signifies not a debtor's last gasp but an opportunity to catch one's breath and recoup. Why has the nation's legal system evolved to allow both corporate and individual debtors greater control over their fate than imaginable elsewhere? Masterfully probing the political dynamics behind this question, David Skeel here provides the first complete account of the remarkable journey American bankruptcy law has taken from its beginnings in 1800, when Congress lifted the country's first bankruptcy code right out.